2014
DOI: 10.1007/s13595-014-0385-1
|View full text |Cite
|
Sign up to set email alerts
|

Potentially increased sawmill yield from hardwoods using X-ray computed tomography for knot detection

Abstract: & Context One of the most important wood defects affecting the value yield from European beech (Fagus sylvatica [L.]) logs is knots that are visible on the sawn wood surface. The non-invasive technology of X-ray computed tomography (CT) can be used for the assessment of log internal features, especially the geometry and position of knots before primary breakdown to support the decision of value-optimised log rotation in sawmills. & Aims The objective of this study was to test whether valueoptimised log rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…In general, application of machines based on such models have provided the most accurate strength grading that has been available on the market in recent years (Hanhijärvi and Ranta-Maunus 2008;Olsson 2016). As regards the possibility of using X-rays to identify knots on the basis of difference in density between knots and clear wood (Oh et al 2009), it should be noted that such density contrasts are generally larger in softwoods than in hardwoods, which implies that knot detection using X-rays is more useful for softwoods than for hardwoods (Stängle et al 2015;Viguier 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, application of machines based on such models have provided the most accurate strength grading that has been available on the market in recent years (Hanhijärvi and Ranta-Maunus 2008;Olsson 2016). As regards the possibility of using X-rays to identify knots on the basis of difference in density between knots and clear wood (Oh et al 2009), it should be noted that such density contrasts are generally larger in softwoods than in hardwoods, which implies that knot detection using X-rays is more useful for softwoods than for hardwoods (Stängle et al 2015;Viguier 2015).…”
Section: Introductionmentioning
confidence: 99%
“…logs based on 38 CT data can improve value yield by about 13 %. Stängle et al (2015) showed that value and 39 volume yield of beech (Fagus sylvatica L.) logs can be increased by up to 24 % when 40 optimizing log rotation based on CT data, compared to an average value from 12 different 41 rotations.…”
mentioning
confidence: 99%
“…Current market prices for sawn wood of each quality grade and the by-products were used to estimate the value increase that would result from the optimized log rotation. Stängle et al (2015) concluded that changing the log rotational angle led to large differences in the volume and value of product yield, as calculated from the sawing simulations, and that potential optimization of volume and value per log was highest for logs of low quality. Based on their results, the authors also indicated that using a CT scanning system to detect log internal defects would allow better performance of hardwood sawmills in the future.…”
Section: Knots and Rameal Tracesmentioning
confidence: 99%